Epic Stories in Dramatic Works - Taubayevich, Koblanov Zholaman; Elepovna , Baltogaeva Zhaili; Tugelbayevna, Zhetkizgenova Aliya; Abdimukhanovna , Karymsakova Baktygul; Daribaevich, Daribaev Samalbay; Kozibayevna , Dalmukhanova Feruza (Journal of Ecohumanism, 2024)
Karakalpak drama on the way of its historical development absorbed the most advanced and exemplary traditions of the great wealth of this people and uses them to this day. The article discusses the features of some Karakalpak dramatic works. At the same time, the article pays great attention to the influence of the literature of the Kazakh people with a close historical fate on the Karakalpak dramaturgy. For example, the dramatic works of Beyimbet Mailin, Zhumat Shanin, Mukhtar Auezov, the search for the disclosure of the secrets of man and time in them, artistic techniques that had a positive impact on Karakalpak playwrights, are narrated on the basis of specific analyses. The methodological basis of the work is the principle of historicism, which contributes to the objective study and evaluation of literary phenomena in the process of evolutionary development. The scientific article uses a traditional set of analysis methods: typological, systemic, comparative.